Lanthanum-based perovskite catalyst and preparation method thereof, modified diaphragm and lithium-sulfur battery

Through the development of the lanthanum-based perovskite catalyst LaNixFe1-xO3, the problems of polysulfide shuttle effect and slow redox reaction kinetics in lithium-sulfur batteries were solved, and the high cycle stability and rate performance of the battery were achieved.

CN119750669APending Publication Date: 2025-04-04ANHUI LEOCH PENEWABLE ENERGY DEV CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411798964.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the discharge process, lithium-sulfur batteries have problems such as polysulfide shuttle effect, slow sulfur redox reaction kinetics and low active sulfur utilization, resulting in poor charging and discharging efficiency and cycling performance of the battery.

Method used

A lanthanum-based perovskite catalyst, LaNixFe1-xO3, was developed to form a unique dense network microstructure through the coordinated regulation of Fe and Ni, introduce Fe atoms to optimize catalytically active sites, and verify the interaction of its high bond energy with polysulfides through density functional theory calculations.

Benefits of technology

The cycle stability and rate performance of lithium sulfur batteries are significantly improved, catalytic activity and stability are enhanced, the redox reaction kinetics of sulfur are optimized, the "shuttle effect" is reduced, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750669A_ABST
    Figure CN119750669A_ABST
Patent Text Reader

Abstract

The invention discloses a lanthanum-based perovskite catalyst and a preparation method thereof, a modified diaphragm and a lithium-sulfur battery, and relates to the technical field of lithium-sulfur batteries. On one hand, the chemical formula of the lanthanum-based perovskite catalyst provided by the invention is LaNi < x > Fe < 1-x > O < 3 >, wherein 0 < x < 1. The preparation method comprises the following steps: respectively mixing a lanthanum source, a nickel source, an iron source, citric acid and ethylenediamine tetraacetic acid, and adding dilute nitric acid to adjust the pH value; stirring in an oil bath pan; washing the product, and performing vacuum drying in an oven to obtain a white product; transferring the white product to 200 DEG C, keeping the temperature for 2 hours, heating to 800 DEG C, and keeping the temperature for 8 hours; and naturally cooling to room temperature to obtain the catalyst. The invention also provides a modified diaphragm coating, a modified diaphragm and a lithium-sulfur battery. In the catalyst provided by the invention, Fe and Ni are synergistically regulated to form B-site mixed coordination, so that diversified electron transfer paths are provided for the electrocatalyst, and the catalytic activity on a polysulfide conversion reaction is improved; and the cycling stability and the rate capability of the lithium-sulfur battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-sulfur batteries, and in particular to lanthanum-based perovskite catalysts and preparation methods, modified diaphragms and lithium-sulfur batteries. Background Art

[0002] Lithium-sulfur batteries have a high theoretical energy density (2600Wh kg -1 ) and sulfur have attracted much attention due to their low cost and environmentally friendly properties. However, their practical application faces many challenges, including: 1. Polysulfide shuttle effect: The intermediate products (Li2S n ,4≤n≤8) are easily dissolved and diffused into the electrolyte, resulting in the loss of positive electrode active materials and the occurrence of negative electrode side reactions; 2. The kinetics of sulfur redox reaction are slow: the electrochemical reaction process of sulfur involves complex multi-electron transfer, and the kinetics are slow, which limits the charge and discharge efficiency of the battery; 3. The utilization rate of active sulfur is low: sulfur-based materials are prone to form "dead sulfur" during the charge and discharge process, which further reduces the capacity and cycle performance. Summary of the invention

[0003] In order to solve at least one of the above technical problems, a catalyst capable of achieving efficient electron transfer, high specific surface area and high activity is developed. The present application provides a lanthanum-based perovskite catalyst and a preparation method, a modified diaphragm and a lithium-sulfur battery.

[0004] On the one hand, the present application provides a lanthanum-based perovskite catalyst, the chemical formula of which is: LaNi x Fe 1-x O3; wherein, 0<x<1.

[0005] Optionally, the present application provides a lanthanum-based perovskite catalyst, the chemical formula of which is: LaNi 0.5 Fe 0.5 O3.

[0006] In a second aspect, the present application provides a method for preparing the above catalyst, comprising the following steps:

[0007] S1. Add lanthanum source, nickel source, iron source, citric acid and ethylenediaminetetraacetic acid into a 500 mL beaker respectively and add dilute nitric acid to adjust the pH to 8;

[0008] S2. Place the beaker in an oil bath at 80°C and stir for 24 hours; after washing the product, dry it in a vacuum oven at 60°C for 12 hours to obtain a white product;

[0009] S3. The white product was transferred to a muffle furnace and maintained at 200°C for 2 hours, then heated to 800°C and maintained for 8 hours; the catalyst was obtained after naturally cooling to room temperature.

[0010] Optionally, the product is washed three times by centrifugation with water and anhydrous ethanol respectively.

[0011] Optionally, in S3, the heating rate is 5°C min -1 .

[0012] Optionally, the lanthanum source is lanthanum nitrate hexahydrate;

[0013] And / or, the nickel source is nickel nitrate hexahydrate;

[0014] And / or, the iron source is ferric nitrate nonahydrate.

[0015] In a third aspect, the present application provides a lithium-sulfur battery modified diaphragm coating, comprising a binder, a conductive agent and the above-mentioned catalyst.

[0016] Optionally, the weight ratio of the binder, the conductive agent and the catalyst is 1:2:7.

[0017] Optionally, the binder is polyvinylidene fluoride, and / or the conductive agent is conductive carbon black.

[0018] In a fourth aspect, the present application provides a modified diaphragm for a lithium-sulfur battery, comprising a diaphragm and the above-mentioned coating, wherein the coating is coated on one side of the diaphragm.

[0019] In a fifth aspect, the present application provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode and the modified diaphragm described above; the modified diaphragm is arranged between the positive electrode and the negative electrode, and the side coated with the coating faces the positive electrode.

[0020] In summary, the lanthanum-based perovskite catalyst synergistically regulated by Fe and Ni exhibits a unique dense network microstructure, which shows obvious advantages in lithium-sulfur batteries, including at least one of the following beneficial effects:

[0021] 1. Introduction and optimization of catalytic active sites: Fe atoms in LaFe 0.5 Ni 0.5 O3 partially replaces the Ni position, forming a mixed coordination at the B site (Fe 3+ / Ni 2+ ); This structure provides a variety of electron transfer pathways for electrocatalysts, improving the catalytic activity for polysulfide conversion reactions;

[0022] 2. Fe 3+ with Ni 2+ The synergistic effect of the two significantly reduces the conversion barrier of sulfide and accelerates the kinetics of sulfur redox reaction;

[0023] 3. The introduction of Fe enhances the interaction with polysulfides through chemical adsorption; density functional theory (DFT) calculations show that Fe has a higher bond energy (M-S bond), which can effectively fix polysulfides on the catalyst surface, reduce their dissolution and diffusion in the electrolyte, and thus inhibit the shuttle effect. Therefore, the introduction of transition metals further improves the catalytic activity and stability of the material, and also significantly improves the overall performance of lithium-sulfur batteries by enhancing the interaction with polysulfides and optimizing the reaction kinetics;

[0024] 4. The lithium-sulfur battery assembled with the diaphragm having electrocatalytic function of the present invention has greatly improved cycle stability and rate performance, and the functional diaphragm of the present invention has a simple preparation process, is easy to operate, and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 XRD pattern of the catalyst LaNiO3 prepared in Preparation Example 2;

[0026] Figure 2 The catalyst LaNi prepared in Preparation Example 1 0.5 Fe 0.5 XRD pattern of O3;

[0027] Figure 3 This is a SEM image of the catalyst LaNiO3 prepared in Preparation Example 2;

[0028] Figure 4 The catalyst LaNi prepared in Preparation Example 1 0.5 Fe 0.5 SEM image of O3;

[0029] Figure 5 is a cycle performance diagram of the lithium-sulfur battery assembled in Example 6;

[0030] Figure 6 This is a rate performance diagram of the lithium-sulfur battery assembled in Example 5. DETAILED DESCRIPTION

[0031] The present application is further described in detail below with reference to the accompanying drawings and embodiments.

[0032] This application designs a lanthanum-based perovskite catalyst with the chemical formula: LaNi x Fe 1-x O3; wherein, 0<x<1.

[0033] The dense network microstructure of the present invention provides more active sites for the catalytic reaction, thereby improving the contact efficiency between the material and the polysulfide in the electrolyte.

[0034] Compared with ordinary lanthanum-based perovskite materials, LaNi x Fe1-x The three-dimensional network structure of O3 effectively improves the electronic and ionic conductivity; it retains the intrinsic conductivity of lanthanum-based perovskite, and adjusts the d orbital electron distribution through the coordinated occupation of B site by Fe and Ni to form Fe 3+ / Ni 2+ The mixed valence state significantly enhances the tunability and reactivity of electrons, and the d-orbital electrons of the B-site transition metal ions achieve efficient electron transfer; the high specific surface area and dense network structure provide abundant exposed active sites, showing multiple selective catalytic results for LiPSs.

[0035] Furthermore, the applicant found that in the above catalyst, x=0.5, that is, the chemical formula is: LaNi 0.5 Fe 0.5 When O3 is used, the structural stability is higher, the catalytic activity is higher, and the conversion barrier of sulfides is lower.

[0036] The present application designs a method for preparing the above-mentioned catalyst, comprising the following steps:

[0037] S1. Add lanthanum source, nickel source, iron source, citric acid and ethylenediaminetetraacetic acid into a 500 mL beaker respectively and add dilute nitric acid to adjust the pH to 8;

[0038] S2. Place the beaker in an oil bath at 80°C and stir for 24 hours; after washing the product, dry it in a vacuum oven at 60°C for 12 hours to obtain a white product;

[0039] S3. The white product was transferred to a muffle furnace and maintained at 200°C for 2 hours, then heated to 800°C and maintained for 8 hours; the catalyst was obtained after naturally cooling to room temperature.

[0040] The present application designs a lithium-sulfur battery modified diaphragm coating, including a binder, a conductive agent and the above-mentioned catalyst; and the coating is coated on one side of the diaphragm to prepare a modified diaphragm, which is used in a lithium-sulfur battery, and the side coated with the coating faces the positive electrode of the lithium-sulfur battery.

[0041] The present invention loads a composite of a catalyst, a conductive agent and a binder on the positive electrode side of a polypropylene diaphragm, and physically restricts PSs by improving the pore size of the diaphragm itself, while simultaneously reacting with the catalyst LaNi loaded on the diaphragm. x Fe 1-x The chemical adsorption and electrocatalytic performance of O3 on LiPSs synergistically inhibit the "shuttle effect" of PSs and improve the cycle stability of lithium-sulfur batteries.

[0042] In the following examples of the present application, unless otherwise specified, the main components involved were purchased from commercially available products. Specific embodiments

[0044] Example 1

[0045] The present application provides a method for preparing a lanthanum-based perovskite catalyst, the chemical formula of which is: LaNi x Fe 1- x O3; wherein, in the embodiment, x is 0.5, that is, the chemical formula is LaNi 0.5 Fe 0.5 O3.

[0046] Lanthanum nitrate hexahydrate, nickel nitrate hexahydrate, ferric nitrate nonahydrate, citric acid, and ethylenediaminetetraacetic acid (the molar ratio of lanthanum nitrate hexahydrate, nickel nitrate hexahydrate, ferric nitrate nonahydrate, citric acid and ethylenediaminetetraacetic acid is 2:1:1:6:4) were added to a 500mL beaker and dilute nitric acid was added to adjust the pH to 8. Subsequently, the beaker was placed in an 80°C oil bath and stirred for 24 hours. The final product was centrifuged and washed three times with water and anhydrous ethanol, respectively, and dried in a vacuum oven at 60°C for 12 hours. The white product was transferred to a muffle furnace and maintained at 200°C for 2 hours, then heated to 800°C and maintained for 8 hours, with a heating rate of 5°C min -1 After cooling naturally to room temperature, the catalyst LaNi 0.5 Fe 0.5 O3.

[0047] Example 2

[0048] The present application provides a method for preparing a lanthanum-based perovskite catalyst, the chemical formula of the catalyst being: LaNiO3.

[0049] Lanthanum nitrate hexahydrate, nickel nitrate hexahydrate, citric acid, and ethylenediaminetetraacetic acid (the molar ratio of lanthanum nitrate hexahydrate, nickel nitrate hexahydrate, citric acid and ethylenediaminetetraacetic acid is 1:1:3:2) were added to a 500mL beaker and dilute nitric acid was added to adjust the pH to 8. Subsequently, the beaker was placed in an 80°C oil bath and stirred for 24 hours. The final product was centrifuged and washed three times with water and anhydrous ethanol, respectively, and dried in a vacuum oven at 60°C for 12 hours. The white product was transferred to a muffle furnace and maintained at 200°C for 2 hours, then heated to 800°C and maintained for 8 hours, with a heating rate of 5°C min -1 After naturally cooling to room temperature, the catalyst LaNiO3 is obtained.

[0050] Figure 1 and Figure 2 The LaNiO3 prepared in Preparation Example 2 and the LaNi prepared in Preparation Example 1 0.5 Fe 0.5 O3's XRD pattern shows that the characteristic peaks of the material coincide with those of the standard XRD structure, which fully demonstrates that LaNiO3 and LaNi 0.5 Fe 0.5 Successful preparation of O3 dense network structure.

[0051] Figure 3 and Figure 4 The LaNiO3 prepared in Preparation Example 2 and the LaNi prepared in Preparation Example 1 0.5 Fe 0.5 SEM image of O3; Figure 3 and Figure 4 From the SEM image, we can see that the original La2O3 structure can still remain intact, and after the addition of Ni and Fe, the originally sparse voids are filled into a dense structure.

[0052] Example 3

[0053] This preparation example is used to prepare a modified diaphragm, and the coating on the modified diaphragm includes a binder, a conductive agent, and the catalyst prepared in Preparation Example 1. The weight ratio of the binder, the conductive agent, and the catalyst is 1:2:7. The binder is exemplarily polyvinylidene fluoride, and the conductive agent is exemplarily conductive carbon black.

[0054] 140 mg of catalyst, 40 mg of CB, and 20 mg of PVDF were weighed separately, mixed and ground thoroughly in a mortar, then transferred to a weighing bottle, an appropriate amount of NMP organic solvent was added, stirred continuously for 12 h, and then evenly coated on the Celgard-2400 diaphragm with a 200 μm spatula, and transferred to an oven at 60°C for vacuum drying overnight to obtain a modified diaphragm.

[0055] Example 4

[0056] This preparation example is used to prepare a modified diaphragm, and the coating on the modified diaphragm includes a binder, a conductive agent, and the catalyst prepared in Preparation Example 2. The weight ratio of the binder, the conductive agent, and the catalyst is 1:2:7. The binder is exemplarily polyvinylidene fluoride, and the conductive agent is exemplarily conductive carbon black.

[0057] 140 mg of catalyst, 40 mg of CB, and 20 mg of PVDF were weighed separately, mixed and ground thoroughly in a mortar, then transferred to a weighing bottle, an appropriate amount of NMP organic solvent was added, stirred continuously for 12 h, and then evenly coated on the Celgard-2400 diaphragm with a 200 μm spatula, and transferred to an oven at 60°C for vacuum drying overnight to obtain a modified diaphragm.

[0058] Example 5

[0059] The cut positive electrode sheet and the modified diaphragm prepared in Example 3 were placed in a glove box, and then the CR2032 button battery was assembled in the order of positive electrode shell, positive electrode, electrolyte, modified diaphragm, electrolyte, negative electrode, gasket, spring and negative electrode shell; the electrolyte used was 1M LiTFSI, DME:DOL=1:1V%, 0.1M LiNO3.

[0060] Example 6

[0061] The cut positive electrode sheet and the modified diaphragm prepared in Example 4 were placed in a glove box, and then the CR2032 button battery was assembled in the order of positive electrode shell, positive electrode, electrolyte, modified diaphragm, electrolyte, negative electrode, gasket, spring and negative electrode shell; the electrolyte used was 1M LiTFSI, DME:DOL=1:1V%, 0.1M LiNO3.

[0062] The charge and discharge performance of the button cells assembled above were tested at room temperature using a LandCT2001A battery testing system and a CHI760E electrochemical workstation.

[0063] Figure 5 This is a graph showing the cycle performance of the lithium-sulfur battery assembled in Example 6. Figure 5 It can be seen from the figure that after activation, its first cycle discharge capacity at 2C is 360.9 mAh / g, and after 160 cycles, its capacity remains at 377.6 mAh / g.

[0064] Figure 6 This is the rate performance diagram of the lithium-sulfur battery assembled in Example 5. 0.5 Fe 0.5 The lithium-sulfur battery assembled with O3-modified diaphragm released a high first-cycle discharge specific capacity of 654.7 mAh / g at 2C after activation, and its capacity remained at 656.9 mAh / g after 160 cycles.

[0065] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A lanthanum-based perovskite catalyst, characterized in that: The chemical formula is: LaNi x Fe 1-x O3; wherein, 0<x<1.

2. The catalyst according to claim 1, characterized in that The chemical formula is: LaNi 0.5 Fe 0.5 O3.

3. A method for preparing the catalyst according to claim 1, characterized in that: The following steps are involved: S1. Add lanthanum source, nickel source, iron source, citric acid and ethylenediaminetetraacetic acid into a 500 mL beaker respectively and add dilute nitric acid to adjust the pH to 8; S2. Place the beaker in an oil bath at 80°C and stir for 24 hours; after washing the product, dry it in a vacuum oven at 60°C for 12 hours to obtain a white product; S3. The white product was transferred to a muffle furnace and maintained at 200°C for 2 hours, then heated to 800°C and maintained for 8 hours; the catalyst was obtained after naturally cooling to room temperature.

4. The catalyst according to claim 1, characterized in that In S3, the heating rate is 5°C min -1 .

5. The preparation method according to claim 1, characterized in that: The lanthanum source is lanthanum nitrate hexahydrate; And / or, the nickel source is nickel nitrate hexahydrate; And / or, the iron source is ferric nitrate nonahydrate.

6. A lithium-sulfur battery modified diaphragm coating, characterized in that: The invention comprises a binder, a conductive agent and the catalyst as claimed in claim 1.

7. The coating according to claim 6, characterized in that The weight ratio of the binder, the conductive agent and the catalyst is 1:2:

7.

8. The coating according to claim 6, characterized in that The binder is polyvinylidene fluoride, and / or the conductive agent is conductive carbon black.

9. A modified separator for a lithium-sulfur battery, characterized in that: The invention comprises a diaphragm and the coating as claimed in claim 6, wherein the coating is coated on one side of the diaphragm.

10. A lithium-sulfur battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the modified separator as claimed in claim 9; the modified separator is arranged between the positive electrode and the negative electrode, and the side coated with the coating faces the positive electrode.